Kemampuan Komunikasi Dan Pemahaman Konsep Aljabar Linier Mahasiswa Universitas Putra Indonesia ‘YPTK’ Padang - Dewimarni, Syelfia (Al-Jabar: Jurnal Pendidikan Matematika, 2017)
This research in a descriptive it was done in academic year 20016/2017. The subject of this research was SI 10 class of UPI YPTK Padang who attended linier algebra class consisted 48 students. Purpose of this research was to give description about students’ ability understanding concept of communication in Liniear algebra class with vector subtopic. Students’ ability and understanding concept of communication was described in a whole, students with high level and student with low level. Research instrumentation was ability and understanding communication concept test. Test result was descripted quantitatively and some of students’ answer was descripted qualitatively. Based on result, for the students’ communication ability 63,58% in a whole, 50,05% in high level and 50% in a low level had ability in a making a presentation with visual or picture to clearer the problem and to facilitate its solution. For students’ understanding in communication concept 65,44% in a whole, 81,34% in high level and 46,29% in low level who understanding concept ability in explain the concept correctly and use the concept in right way.